Outcomes of B-Cell-Depleted Patients With Coronavirus Disease 2019 Treated With Antispike Monoclonal Antibodies. (14th April 2022) - Yetmar, Zachary A; Khodadadi, Ryan B; Seville, Maria Teresa; Brumble, Lisa; O'Horo, John C; Ganesh, Ravindra; Razonable, Raymund R
Abstract: Antispike monoclonal antibody treatment of 180 B-cell-depleted patients with mild-to-moderate coronavirus disease 2019 (COVID-19) resulted in good outcomes overall, with only 12.2% progressing to severe disease, 9.4% requiring hospitalization, 0.6% requiring mechanical ventilation, no deaths within 30 days, and 1.8% developing persistent COVID-19. Antispike monoclonal antibodies appear effective in this immunocompromised population.